2013
DOI: 10.1089/cyber.2012.0328
|View full text |Cite
|
Sign up to set email alerts
|

Blaming the Victim: The Effects of Extraversion and Information Disclosure on Guilt Attributions in Cyberbullying

Abstract: Cyberbullying victims' success in coping with bullying largely depends on schoolmates and other bystanders' social support. However, factors influencing the degree of social support have as yet not been investigated. In this article, the concept of victim blaming is applied to cyberbullying incidents. It is assumed that a cyberbullying victim receives less social support when the victim's behavior is perceived as very overt. It is further assumed that this effect's underlying process is the partial attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 38 publications
5
53
1
7
Order By: Relevance
“…These findings may be seen in light of and have implications for knowledge on the actual personality of targets and bullies (Nielsen et al, 2017). Yet, the results may also be related to and have implications for knowledge on observers’ attribution of traits (see also Weber et al, 2013). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These findings may be seen in light of and have implications for knowledge on the actual personality of targets and bullies (Nielsen et al, 2017). Yet, the results may also be related to and have implications for knowledge on observers’ attribution of traits (see also Weber et al, 2013). …”
Section: Discussionmentioning
confidence: 86%
“…In addition, people with low scores on Extraversion often receive less social support (Swickert et al, 2002), which also may make them more likely than others to become targets of bullying. However, in an experimental study of cyberbullying it was shown that participants attributed more responsibility for a bullying incident to the victim when the victim was presented as extraverted than when the victim was presented as less extraverted (Weber et al, 2013). No significant differences between conditions were found for Openness.…”
Section: Discussionmentioning
confidence: 99%
“…While it is common for dental professionals to criticize their patients for their poor oral hygiene and consequent dental diseases, Chandu (2011) highlighted that patients may perceive such criticisms as a lack of empathy and understanding [20]. The victim-blaming attitude is more problematic than beneficial; health professionals should take into account a patient’s life situation and environmental factors such as low level of knowledge or inability to access adequate resources without stereotyping them [21,22]. As advised by Bedos and Loignon (2011), a paternalistic approach lacks efficacy and is in direct contradiction to the more humanistic patient-centred care approach [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to help patients cope with their decreased sense of power, emphasis needs to be placed on communication, empathy and rapport building skills [22,30] as well as actively involving them in a shared decision-making process. In fact, participants’ positive experiences seemed to have occurred because dentists showed respect and compassion through effective communication, which may have led to an acceptable balance in the power relationship [5].…”
Section: Discussionmentioning
confidence: 99%
“…This stress can add to the psychological burden of the experience especially when the issue of victim blaming is concerned (Gini, 2008). Indeed, many researchers have noted that social support (as opposed to victim-blaming) plays a genuine role in how individuals cope with cyberbullying incidents (Weber et al, 2013). As such, anti-bullying policies and awareness campaigns are naturally limited because the influence of social dynamics (e.g., social support and peer relationships etc.)…”
Section: Who Is Responsible?mentioning
confidence: 99%